Paciente femenino de 44 años de edad con hipertensión no controlada y obesidad grado II. - Díaz Avegno, Jennipher Meilyn (2020)
The present case deals with a 44-year-old female patient, married, mother of six children, teacher, with a family pathological history in mother with hypertension, father with type II diabetes mellitus, history. Surgical three years ago performed laparoscopic gallbladder surgery, she does not refer to allergies, active smoking habits seven cigarettes a day, two months ago she was diagnosed with high blood pressure. He comes to the consultation for presenting for a few days very constant headaches, blurred vision, dizziness, nausea, his blood pressure at the time of the consultation is 139 / 93mmHg, he undergoes complementary tests which reflected high values in his cholesterol and triglycerides Furthermore, her BMI of 37.5kg / m2 gives us a diagnosis of grade II obesity with severe cardiovascular risk, which is why she is referred to the nutritionist for immediate intervention in order to avoid complications in her health. An individualized diet appropriate to her existing pathologies is prescribed, the patient prepared to collaborate with the nutritional treatment then she was given an appointment at 20 days for follow-up and monitoring where changes in her health status were evidenced from the first appointment, improving your weight and keeping cholesterol and triglycerides at normal values.